2014
DOI: 10.3892/mmr.2014.2129
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic investigations of the interaction of the anti-hypertension drug valsartan with human serum albumin

Abstract: The aim of the present study was to investigate the interaction between valsartan, an anti-hypertension drug, and human serum albumin (HSA) using spectroscopic techniques, including fluorescence, ultraviolet-visible absorption, synchronous fluorescence and circular dichroism (CD). The results demonstrated that valsartan and HSA form a complex and that a static quenching mechanism occurs. In addition, the binding constant and the number of binding sites for valsartan on HSA were analyzed. Hydrophobic interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Table 3. The negative ΔG indicated that the formation of complex of taxifolin and αglucosidase was spontaneous while the negative ΔH and ΔS suggested that the conformation of the complex was maintained by van der Waals and hydrogen bonds according to the previous studies [16,17]. The molecular docking method is widely used to study the binding modes of enzymes and inhibitors.…”
Section: Npc Natural Product Communicationsmentioning
confidence: 97%
“…Table 3. The negative ΔG indicated that the formation of complex of taxifolin and αglucosidase was spontaneous while the negative ΔH and ΔS suggested that the conformation of the complex was maintained by van der Waals and hydrogen bonds according to the previous studies [16,17]. The molecular docking method is widely used to study the binding modes of enzymes and inhibitors.…”
Section: Npc Natural Product Communicationsmentioning
confidence: 97%
“…The interaction between the emission peak of trypsin and AE showed a red shi of 1 nm (from 277 nm to 278 nm), which indicated that hydrophobicity decreased and polarity increased in the Trp microenvironment due to AE insertion. 25 In addition, with the increase of AE concentration, the uorescence intensity at Dl ¼ 60 nm decreased steadily, which supported the uorescence quenching when AE interacts with trypsin. For Tyr residue with Dl ¼ 15 nm, the emission peak decreased with the increase of AE concentration, but the maximum emission wavelength did not change signicantly, indicating that the microenvironment around Tyr residue was less disturbed.…”
Section: Synchronous Uorescence Spectramentioning
confidence: 67%
“…Other than albumin and globulin, body fluids such as serum are also rich in mineral ions hence the need for experimental cases E and F which elucidated additional synergism due to presence of the mineral ions. At normal body pH, albumin in serum binds cations such as sodium, copper and zinc as well as other exogenous ligands like drugs which synergistically alter the dielectric properties of serum. The strong binding is supported by improved hyponatremia following albumin infusion .…”
Section: Discussionmentioning
confidence: 99%
“…Serum albumin contains 585 amino acids which includes a single tryptophan Trp‐214 residue in its hydrophobic cavity among other large aromatic amino acids like tyrosine (Figure c), and phenyl alanine . When albumin is subjected to electric current, re‐orientation of its amino acids occurs.…”
Section: Discussionmentioning
confidence: 99%